2022
DOI: 10.7577/seminar.4692
|View full text |Cite
|
Sign up to set email alerts
|

Learning Outcomes in HMD-VR: a Literature Review

Abstract: While the educational technology has developed to the point that Extended Reality (XR), including immersive Virtual Reality (VR) can be used in education, the learning outcomes of these technologies in the large scale is still quite unknown. This literature review aims to take a comprehensive look to the field of immersive VR in to find out where the learning outcomes of HMD-VR stands out, and how they compare to other technologies and methods. The main result of this paper is that while HMD-based Virtual Real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Despite the generally positive attitude of researchers toward virtual reality technology, the available research has focused more on the impact of virtual reality technology on learners' academic achievement and lacks research on the impact on learners' academic experience. Lähtevänoja et al (2022) suggested that the impact on indirect learning outcomes (e.g., motivation and engagement in learning) should be added to future research.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the generally positive attitude of researchers toward virtual reality technology, the available research has focused more on the impact of virtual reality technology on learners' academic achievement and lacks research on the impact on learners' academic experience. Lähtevänoja et al (2022) suggested that the impact on indirect learning outcomes (e.g., motivation and engagement in learning) should be added to future research.…”
Section: Introductionmentioning
confidence: 99%